Virulência de isolados Dexanthomonas campestris pv. Phaseoli (Smith) dye em feijoeiro - Maringoni, Antonio Carlos [UNESP] (My University, 1998)
The objective of this research was to evaluate de reaction of leaves and pods of five cultivars of bean (Phaseolus vulgaris L.) plants to twenty strains of Xanthomonas campestris pv. phaseoli. The strains were inoculated onto leaves in a greenhouse, and onto pods in a growth chamber. The results obtained were analyzed and the strains classified into three groups: low, medium, and high virulence. Most of the strains showed high virulence on leaves of Carioca and Rio Negro cultivars, as opposed to only low to medium virulence on leaves of IAPAR 14, IAPAR 16, and G. N. Nebraska # 1 sel. 27 cultivars. There were, however, individual strains powerful enough to overcome the leaf resistance of IAPAR 14, IAPAR 16, and G. N. Nebraska # 1 sel. 27. With regard to pods, most strains showed high virulence on all bean cultivars, with exception of IAPAR 14 where virulence was at medium level. A correlation between leaf and pod symptoms was found to exist in Carioca, Rio Negro, and IAPAR 14 cultivars. No such correlation was observed in IAPAR 16 and G. N. Nebraska # 1 sel. 27. Comparing strains producing melanine in vitro with those not producing this pigment, no difference was observed with regard to virulence.

O presente trabalho teve por objetivo avaliar a reação das folhas e vagens de cinco cultivares de feijoeiro (Phaseolus vulgaris L.) a vinte isolados de Xanthomonas campestres pv. phaseoli. Os experimentos foram conduzidos em condições de casa-de-vegetação (inoculação foliar) e de estufa (inoculação em vagem). Pela análise dos resultados, os isolados puderam ser agrupados em três classes de virulência. A maioria dos isolados apresentaram alta virulência nas folhas das cultivares Carioca e Rio Negro, e baixa a média virulência nas folhas das cultivares IAPAR 14, IAPAR 16 e G. N. Nebraska # 1 sel. 27. Houve, porém, isolados que conseguiram vencer a resistência foliar das cultivares IAPAR 14, IAPAR 16 e G. N. Nebraska # 1 sel. 27. Quanto a vagem, a maioria dos isolados apresentaram alta virulência nas cultivares Carioca, Rio Negro, IAPAR 16 e G. N. Nebraska # 1 sel. 27, e média virulência na cultivar IAPAR 14. Houve correlação entre os sintomas foliar e de vagem das cultivares Carioca, Rio Negro e IAPAR 14. Não houve correlação entre os sintomas foliar e de vagem das cultivares IAPAR 16 e G. N. Nebraska # 1 sel. 27. Não foi verificada diferença na virulência entre isolados produtores e não-produtores de melanina in vitro.
Virulence of Xanthomonas campestris pv. Phaseoli (Smith) dye strains on bean plants
Keywords: Common bean blight; Phaseolus vulgaris; Resistance